2013
DOI: 10.1002/ggge.20253
|View full text |Cite
|
Sign up to set email alerts
|

New aero‐gravity results from the Arctic: Linking the latest Cretaceous‐early Cenozoic plate kinematics of the North Atlantic and Arctic Ocean

Abstract: [1] The tectonic history of the Arctic Ocean remains poorly resolved and highly controversial. Details regarding break up of the Lomonosov Ridge from the Barents-Kara shelf margins and the establishment of seafloor spreading in the Cenozoic Eurasia Basin are unresolved. Significantly, the plate tectonic evolution of the Mesozoic Amerasia Basin is essentially unknown. The Arctic Ocean north of Greenland is at a critical juncture that formed at the locus of a Mesozoic three-plate setting between the Lomonosov Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 62 publications
1
54
0
Order By: Relevance
“…Therefore, their common geological nature can be assumed. The magnetic field of the Lomonosov Ridge is not reflected as a cohesive structure of the interference type, which is almost indistinguishable from the magnetic anomalies of the Marvin Spur and Alpha Ridge [Døssing et al, 2013].…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Therefore, their common geological nature can be assumed. The magnetic field of the Lomonosov Ridge is not reflected as a cohesive structure of the interference type, which is almost indistinguishable from the magnetic anomalies of the Marvin Spur and Alpha Ridge [Døssing et al, 2013].…”
Section: Introductionmentioning
confidence: 61%
“…Magnetic anomalies of the Amerasian province abruptly cut off by a fault zone in the area of Greenland and Arctic Canadian Archipelago along the continental slope, but then, on the coast of the North American continent observed magnetic anomalies are similar to the anomalies of the Alpha and Lomonosov ridges [Døssing, 2013;Funck et al, 2011].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Dossing et al [9] suggested that the Eurekan event may have affected the southern part of the Lomonosov Ridge and also could have triggered a certain amount of compression in the southern Eurasian Basin that resulted in volcanism and even subduction. The lack of fracture zones in the Eurasian Basin makes it difficult to track changes in spreading direction, but we would like to point out that a certain change in isochron orientation is visible in the magnetic anomaly data northwest of the Kara Sea (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In some areas, the faults were reactivated during SE-directed thrust tectonics in Mid-Eocene The idea of Eurekan deformation affecting areas beyond the Ellesmere Islands has been put forward in recent studies which combined knowledge of crustal structure from new geophysical data with results from modeling, and shows that the oceanic Amundsen Basin, the continental Lomonosov Ridge and the Morris Jessup Rise were all disturbed by significant Eurekan compression [10]. In particular, Dossing et al [9] suggested that Eurekan crustal shortening contributed to the formation of the distinct Lomonosov Ridge plateau against an important fault zone north of Greenland.…”
Section: Eurekan Orogenymentioning
confidence: 99%